PENGEMBANGAN KOMODITAS KOPI MELALUI PENGUATAN KAPASITAS TEKNIS DAN MANAJERIAL PETANI DI DESA KURRAK - Suryani Dewi; Arman Amran; Andi Werawe Angka; Dian Utami Zainuddin; Irwan Samad; Asrul Hidayat; Fitri Fitri (LPPM Universitas Al Muslim, 2023)
Kurrak Village Tapango District Polewali Mandar Regency has topography that met the criteria of the environmental requirements for growing Arabica and Robusta Coffee. Efforts to develop coffee commodities in Kurrak Village confronted by various problems, so that it requires the role and support of various institutions, both government, educational institutions and private institutions. Problems with coffee development range from the on-farm sector to the off-farm sector. The problems faced by farmers were the low knowledge of farmers in the technical application of good coffee cultivation and the low level of knowledge of farmer families in managing farming finances thus resulting in lack of farming capital of the farmers. This community empowerment through the Hadji Kalla Foundation's CSR program aimed to provide improvements to the on-farm sector in increasing farmer capacity, changing mindsets and increasing farming managerial capabilities. Empowerment methods used were counseling and mentoring. The results achieved were that farming families in Kurrak Village had sufficient capacity to apply Good Agriculture Practices (GAP) to coffee cultivation techniques and had knowledge of financial management in plantation farming, especially coffee plants.